Good for the Wallet - Good for the Planet: Do Environmental and Financial Performance Lead to Climate-related Disclosure of Asia-Pacific Companies? - Sholihin, Mahfud; Barokah, Zuni; Agustin, Apia Dewi (The Indonesian Journal of Accounting Research, 2025)
This study investigates the relationship between corporate environmental performance and climate-related disclosure, and whether financial performance mediates that relationship, based on signalling theory and legitimacy theory. The analysis was based on 5,258 firm-year observations from non-financial companies in the Asia-Pacific region that participated in the Carbon Disclosure Project (CDP) climate change disclosure survey during 2016–2023. The findings indicate that company’s environmental performance positively affects the level of climate-related disclosures. Further analysis reveals that the effect of environmental performance on climate-related disclosures is mediated by the company’s financial performance.